The Igbo Anglican Church (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2024)
"The Igbo Anglican Church" is a story of my first encounter with a Nigerian diaspora community in the US. It's a story that captures the feeling of seeking connection in unfamiliar places as an immigrant, the awkwardness of not fully fitting in within your culture, and the humorous yet poignant contradictions that define immigrant community attempts to hold onto their “roots” in a place far from home. This piece invites a personal reflection on the nuances of identity, belonging, and the eternal dance between tradition, defiance, and assimilation in a new society.